PERAN MOTIVASI KERJA DALAM MEMEDIASI PENGARUH LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN - Nuru Kalumidya Erponis (Yayasan Education and Social Center, 2026)
Employee productivity is a strategic issue for organizations because productivity reflects the ability of employees to produce quality output effectively, efficiently, and sustainably. A conducive work environment can support concentration, comfort, cooperation, and work discipline, while poor working conditions may reduce enthusiasm and hinder productivity. Work motivation is positioned as a mediating variable because a supportive work environment does not only affect productivity directly, but also increases employee enthusiasm, commitment, responsibility, and persistence in completing tasks. This article aims to analyze the role of work motivation in mediating the effect of the work environment on employee productivity. This study uses a qualitative literature review method by examining theories and previous studies related to work environment, work motivation, and employee productivity. The results of the discussion indicate that the physical and non physical work environment can strengthen productivity when employees feel motivated to work optimally. Work motivation plays an important role as a psychological mechanism that converts environmental support into productive work behavior. The study recommends that organizations improve workplace facilities, interpersonal relationships, leadership support, reward systems, career clarity, and recognition to strengthen employee motivation and productivity.